Relieving Anxiety in Facing the Workplace for Students: The Role of Self-efficacy, Adversity Quotient, Socioeconomic Status and Perceived Social Support - Sopiah Sopiah; Etta Mamang Sangadji; Mahirah Kamaludin (Universitas Negeri Malang, 2021)
Preparing students’ in entering the workforce is a challenge and understanding the determinant factors affecting students anxiety will useful in understanding phenomenon. This study aims to examine internal and external factors affecting students anxiety in facing the world of work. In detail, the research involved self efficacy, adversity quotient, socioeconomic status and perceived social support to explain students’ anxiety. Using both online and offline questionnaires, approximately 654 participant were involved with simple random technique sampling. Accordingly, the completed data were analyzed using Structural Equation Modelling with SmartPLS. The findings indicate that internal factors (self-efficacy, and adversity quotient, and external factors (socioeconomic status and perceived social support) have a significant influence on anxiety facing the world of work among advanced students in Indonesia. Keywords: self-efficacy, adversity quotient, socioeconomic status, perceived social support, relieving anxiety.